(untitled) (Zoological Records and Reviews, 2024)
Freshwater ecosystems are among the most pollution-impacted habitats on Earth, yet multi-stressor assessments that simultaneously characterise the effects of nutrient enrichment, organic loading, micropollutants, and heavy metals on animal community structure remain rare across the Scandinavian and Northern European context. This study quantifies the individual and combined effects of four pollution categories on macroinvertebrate, fish, and amphibian communities across 36 freshwater sites spanning a pollution gradient in Sweden, Finland, and Denmark (n = 12,418 individual records, 2021-2023). Nutrient enrichment (total phosphorus > 0.10 mg/L) was the most prevalent stressor (present at 72.2% of sites), significantly reducing EPT (Ephemeroptera, Plecoptera, Trichoptera) richness by 48.3 +- 6.1% relative to reference sites (GLMM: z = 6.84, p < 0.001). Organic pollution (BOD5 > 4 mg/L) reduced fish species richness by 34.7 +- 5.8% and shifted assemblages towards pollution-tolerant cyprinids. Micropollutant mixtures (pharmaceutical compounds, pesticide residues) at peri-urban sites were associated with intersex prevalence of 31.4 +- 7.2% in roach (Rutilus rutilus), consistent with endocrine disruption by estrogenic compounds. Heavy metal gradients (Cu, Zn, Pb) in mine-affected streams correlated negatively with macroinvertebrate ASPT scores (r = -0.81, p < 0.001). Multi-stressor interaction analysis revealed predominantly additive effects of nutrient and organic stressors on EPT richness, but synergistic effects of micropollutants combined with nutrient enrichment on fish endocrine endpoints. These findings provide stressor-specific management targets for achieving EU Water Framework Directive good ecological status in Scandinavian and Northern European rivers.